Probiotic extracellular vesicles engineering for colorectal cancer - Tan, Jing Ren (Nanyang Technological University, 2024)
Colorectal cancer (CRC) has been one of the leading causes for cancer-related deaths globally. The gut microbiome possesses a plethora of bacteria that can help or harm the body. Akkermansia muciniphila is a probiotic in the gut microbiome which has benefits to supplement the treatment of colorectal cancer. One way to deliver Akkermansia muciniphila into the gut is through extracellular vesicles (EVs). Mimetic EVs have a higher yield efficiency than naturally-derived EVs. In this study, we isolated naturally-derived EVs and executed a protocol to extrude mimetic EVs from Akkermansia muciniphila culture. The concentrations and physical dimensions of the EVs were characterised by Bicinchoninic acid (BCA) assay and Nanoparticle Tracking Analysis (NTA) after purification by size exclusion chromatography (SEC). A greater yield of mimetic EVs was obtained than natural EVs and both were used for in vitro test on RAW264.7 cells. The EVs’ immunogenicity was compared using a quantitative polymerase chain reaction (qPCR) method to determine the gene expression levels of pro-inflammatory and anti-inflammatory cytokines. The results suggest that mimetic EVs generally induce lower expression levels than their naturally-derived counterpart, but further investigations can be executed to uncover the therapeutic effects that EVs have in the treatment of CRC.